E-Learning Sebagai Media Pembelajaran (Studi Kasus: STBA Technocrat Tangerang) - Linda Apriyanti; Surdi Supriyadi; Yus Jayusman (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2021)
The implementation of e-learning learning helps students to facilitate the learning process if they cannot attend class. STBA Technocrat has not used e-learning in the use of technology for learning media. Some of the lecturers and students at STBA Technocrat are mostly private employees. Therefore the creation of e-learning is for learning media. To achieve these objectives the author uses a research method approach, namely field studies and literature studies and the development and design of systems with the waterfall and UML models. Using PHP and MySQL programming languages. The conclusion is that with e-learning it can help facilitate lecturers and students in delivering and receiving material so that the teaching and learning process runs quickly not affected by place and time.